Characteristics of Non-Strabismus Binocular Vision Anomalies Patient Attending Tertiary Eye Hospital of Eastern Nepal - Adhikari, Pankaj Ray; Chaudhary , Nirmala; Chaudhary, Bal Krishna; Patel, Pradeep Kumar; Karn , Rajiv Ranjan (Journal of Nobel Medical College, 2026)
Background: Non-Strabismic Binocular Vision Anomalies are visual disorders that affect the subject’s binocular vision and visual performance, especially when performing tasks requiring near vision. Undiagnosed binocular vision and oculomotor dysfunction may present with discomfort which can have a negative impact on academic performance. The objective of this study was to assess characteristics of NSBVAs patient attending at tertiary eye hospital of Nepal. Materials and Methods: This was hospital based cross-sectional study done at Biratnagar Eye Hospital, Biratnagar, Nepal from July –December 2022. All consenting patients having asthenopic symptoms like headache, difficulty in doing near work from age group 10-40 years referred to VT clinic for further evaluation were included in the study while patient with binocular vision anomalies secondary to strabismus, amblyopia, anisometropia (> 2.00 Diopters), any other ocular pathology, any ocular surgery, and neurological disorders were excluded from the study. Results: A total 852 eyes of 426 patients were enrolled during the study period who met the inclusion criteria. Majority of them were female 287(67.1%) and students 268(62.9%) were more referred for orthoptic evaluation. NSBVAs was found in 306 (71.8%) among them majority had convergence related problem 172 (56.2%) and mostly found in less than 30 years of age 257(84%). Different vision therapy exercises were advised to needy patients. Conclusion: Non-strabismus binocular vision anomalies were common problem in all asthenopic patients less than 30 years of age who had more near work and it was treated with proper vision therapy exercises.